Response to Invited Reaction Articles 1 and 2. (December 2022) - Wang, Greg G.; Doty, D. Harold
We offer our response to the two Invited Reaction papers that identify interesting and legitimate challenges to our theorizing study. In the sense-making process of interpreting the critiques, we discovered that the challenges were rooted in deeper issues related to broader theory building processes and approaches. Thus, our response is particularly focused on exploring how these challenges may inform and guide future theorizing efforts. We organize our response in four primary aspects raised: (1) generalizing from small N samples, (2) singularity in the unit of theory, (3) challenges associated with typological theories, and (4) challenges in the theoretical specification process. We hope that our theorizing and the ongoing dialogues establish a solid starting point that identifies promising opportunities for future human resource development research and generates more interest that other scholars will extend our theorizing and validation efforts.